PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) DENGAN MENGGUNAKAN MODEL JIGSAW DI SEKOLAH DASAR - Rafhi Febryan Putera; Yesi Anita; Hasmai Bungsu Ladiva (Universitas Negeri Padang, 2018)
The result of the research indicated that there was an improvement on the students learning achievement after jigsaw cooperative model applied. This could be seen from: (1) the lesson plan used by teacher is getting complex in which its average score improved from 74,99% in the first cycle into 89,28% in the second cycle, (2) the teachers activity improved from 79,8% in the first cycle into 89,80% in the second cycle, and (3) the students learning achievement 78,69% in the first cycle into 93,26% in the second cycle. Based on this result, it was concluded the use of jigsaw cooperative model could improve the students learning achievement in civics. Keywords: Civic Learning, Jigsaw Model